Developmental exposure to glyphosate-based herbicide and depressive-like behavior in adult offspring: Implication of glutamate excitotoxicity and oxidative stress. (15th July 2017) - Cattani, Daiane; Cesconetto, Patrícia Acordi; Tavares, Mauren Kruger; Parisotto, Eduardo Benedetti; De Oliveira, Paulo Alexandre; Rieg, Carla Elise Heinz; Leite, Marina Concli; Prediger, Rui Daniel Schröder; Wendt, Nestor Cubas; Razzera, Guilherme; Filho, Danilo Wilhelm; Zamoner, Ariane
Graphical abstract: Highlights: Glyphosate-based herbicide leads to glutamate neurotoxicity;. Long-term exposure to glyphosate is a risk factor for depression;. Oxidative stress is involved in glyphosate-induced neurotoxicity;. Glyphosate binds to NMDA receptor leading to Ca 2+ influx. Abstract: We have previously demonstrated that maternal exposure to glyphosate-based herbicide (GBH) leads to glutamate excitotoxicity in 15-day-old rat hippocampus. The present study was conducted in order to investigate the effects of subchronic exposure to GBH on some neurochemical and behavioral parameters in immature and adult offspring. Rats were exposed to 1% GBH in drinking water (corresponding to 0.36% of glyphosate) from gestational day 5 until postnatal day (PND)-15 or PND60. Results showed that GBH exposure during both prenatal and postnatal periods causes oxidative stress, affects cholinergic and glutamatergic neurotransmission in offspring hippocampus from immature and adult rats. The subchronic exposure to the pesticide decreasedL -[ 14 C]-glutamate uptake and increased 45 Ca 2+ influx in 60-day-old rat hippocampus, suggesting a persistent glutamate excitotoxicity from developmental period (PND15) to adulthood (PND60). Moreover, GBH exposure alters the serum levels of the astrocytic protein S100B. The effects of GBH exposure were associated with oxidative stress and depressive-like behavior in offspring on PND60, as demonstrated by the prolonged immobility time and decreased time of climbing observed in forced swimming test. The mechanisms underlying the GBH-induced neurotoxicity involve the NMDA receptor activation, impairment of cholinergic transmission, astrocyte dysfunction, ERK1/2 overactivation, decreased p65 NF-κB phosphorylation, which are associated with oxidative stress and glutamate excitotoxicity. These neurochemical events may contribute, at least in part, to the depressive-like behavior observed in adult offspring.